Comments on “Probiotic Bifidobacterium strains and galactooligosaccharides improve intestinal barrier function in obese adults but show no synergism when used together as synbiotics” - Ranneh, Yazan; M. Mahmoud, Ayman; Fadel, Abdulmannan; Abu Bakar, Mohd Fadzelly; Md Akim, Abdah (Frontiers, 2023)
Department of Nutrition and Dietetics, College of Pharmacy, Al-Ain University, Al-Ain, United Arab Emirates, 2 Zoology Department, Faculty of Science, Physiology Division, Beni-Suef University, Beni-Suef, Egypt, 3 Department of Life Sciences, Faculty of Science and Engineering, Manchester Metropolitan University, Manchester, United Kingdom, 4 School of Sport and Exercise Sciences, Liver-Pool John Moores University, Liverpool, United Kingdom, 5 Faculty of Applied Sciences and Technology, Universiti Tun Hussein Onn Malaysia (UTHM), Pagoh, Johor, Malaysia, 6 Department of Biomedical Sciences, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Serdang, Selangor, Malaysia